New species of Hopperia (Nematoda, Comesomatidae) and Metachromadora (Nematoda, Desmodoridae) from Patagonia, Chubut, Argentina - de Ward, Catalina T. Pastor (Zootaxa, 2004)
One new Comesomatidae species and one new Desmodoridae species from the Gulfs of San Jos and San Mat as, Chubut province are described: Hopperia patagonica sp. n. is characterized by the shape of odontia on anterior end (one big and two smaller teeth on each); odontia length in relation to the amphid length; values of b and R3, short body length (L: 1370 1500 m) and the de Man s ratios ( b: 10.3 11.7). Metachromadora zaixsi sp. n. is characterized by the absence of pre-cloacal supplements, the presence of four cephalic setae and the de Man s ratios (b: 4.7 7.2). Keys are provided for both species.